President’s Message - Khotar, Rupinder (Operating Room Nurses Association of Canada Journal, 2014)
I find the above quote to be sound advice from an otherwise comic lady. Working with like-minded individuals can be easy and allow for quick decision making and immediate gratification. Profound and longlasting changes that result in positive influence come, however, from ideas that have been developed, challenged and debated. In the pursuit of excellence there is nothing as rewarding as a good debate as long as it’s honest, passionate, and thoughtprovoking. Individuals who apply themselves to the goal of achieving the best possible outcome are open to being challenged and to challenging others. They are the people who inspire others. The ORNAC Board is a reflection of this mindset and commitment to the best.